Epigenetic Alterations and Biomarkers for Immune Checkpoint Inhibitors–Current Standards and Future Perspectives in Malignant Pleural Mesothelioma Treatment - Yoshikawa, Yoshie; Kuribayashi, Kozo; Minami, Toshiyuki; Ohmuraya, Masaki; Kijima, Takashi (Frontiers in Oncology, 2020)
Malignant pleural mesothelioma (MPM) is strongly associated with occupational or environmental asbestos exposure and arises from neoplastic transformation of mesothelial cells in the pleural cavity. The only standard initial treatment for unresectable MPM is combination chemotherapy with cisplatin (CDDP) and pemetrexed (PEM). Further, CDDP/PEM is the only approved regimen with evidence of prolonged overall survival (OS), although the median OS for patients treated with this regimen is only 12 months after diagnosis. Thus, the development of new therapeutic strategies has been investigated for approximately 20 years. In contrast to recent advances in personalized lung cancer therapies, diagnostic and prognostic biomarker research has just started in mesothelioma. Epigenetic alterations include DNA methylation, histone modifications, and other chromatin-remodeling events. These processes are involved in numerous cellular processes including differentiation, development, and tumorigenesis. Epigenetic modifications play an important role in gene expression and regulation related to malignant MPM phenotypes and histological subtypes. An immune checkpoint PD-1 inhibitor, nivolumab, was approved as second-line therapy for patients who had failed initial chemotherapy, based on the results of the MERIT study. Various clinical immunotherapy trials are ongoing in patients with advanced MPM. In this review, we describe recent knowledge on epigenetic alterations, which might identify candidate therapeutic targets and immunotherapeutic regimens under development for MPM.